2019
DOI: 10.3847/1538-4357/ab223c
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the 20 day Superorbital Modulation in the High-mass X-Ray Binary IGR J16493-4348

Abstract: We report on Nuclear Spectroscopic Telescope Array (NuSTAR), Neil Gehrels Swift Observatory (Swift) X-ray Telescope (XRT) and Swift Burst Alert Telescope (BAT) observations of IGR J16493-4348, a wind-fed Supergiant X-ray Binary (SGXB) showing significant superorbital variability. From a discrete Fourier transform of the BAT light curve, we refine its superorbital period to be 20.058 ± 0.007 days. The BAT dynamic power spectrum and a fractional root mean square analysis both show strong variations in the amplit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…If 4U 1538−52 was fainter, it would not have been possible to detect the superorbital modulation as the su-perorbital peak in the power spectrum is much smaller than the orbital peak. The difficulty of detecting superorbital modulation is compounded when the modulation can either decrease in strength, as in IGR J16493-4348 (Coley et al 2019) or 2S 0114+650 (Hu et al 2017), or change modulation shape, as for 4U 1538−52. Thus the possibility remains that low-level superorbital modulation could be present in other similar systems where it has not yet been seen because they are either fainter and/or the superorbital modulation is less persistent.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…If 4U 1538−52 was fainter, it would not have been possible to detect the superorbital modulation as the su-perorbital peak in the power spectrum is much smaller than the orbital peak. The difficulty of detecting superorbital modulation is compounded when the modulation can either decrease in strength, as in IGR J16493-4348 (Coley et al 2019) or 2S 0114+650 (Hu et al 2017), or change modulation shape, as for 4U 1538−52. Thus the possibility remains that low-level superorbital modulation could be present in other similar systems where it has not yet been seen because they are either fainter and/or the superorbital modulation is less persistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the most recent observations (after ∼MJD 57,650) there is a distinct change in the modulation profile which results in the decrease of the peak at the fundamental in the power spectrum and the presence of a peak near the second harmonic of the period. For comparison, in IGR J16493-4348 BAT observations also showed changes in the strength of the superorbital modulation (Coley et al 2019), but with the modulation preserving the phase and shape of the modulation before and after an interval where the modulation significantly weakened. Similarly, for 2S 0114+650 Hu et al (2017) reported that the superorbital period was stable, but that the modulation amplitude was highly variable.…”
Section: U 1538−52mentioning
confidence: 98%
See 2 more Smart Citations
“…In this case, the superorbital modulation is produced by a single-arm CIR with a rotational period of 10.3 days. Coley et al (2019) presented an attempt to observationally understand the nature of the superorbital modulation in IGR J16493−4348. They combined an analysis of long-term intensity changes traced via Swift BAT with a broad-band spectral analysis combining two quasi-simultaneous Swift XRT and NuSTAR observation at the maximum and minimum phase of the superorbital modulation within a single 20 days cycle.…”
Section: Superorbital Modulationsmentioning
confidence: 99%